Discipline as Prevention: Psychoeducational Strategies in Internet Sexual Offending Group Programs - Rimer, Jonah R. (International journal of offender therapy and comparative criminology, 2021)
This paper analyzes a UK-based psychoeducational intervention for users of online child sexual exploitation material (CSEM). It is founded on 17 months of anthropological research in group programs with 81 participants and 15 staff. The article argues that group exercises help participants reframe knowledge about their offending, and ultimately reinforce the theoretical concept of discipline (Foucault) toward internal and external surveillance, normalization, and decreased risk. The paper first discusses factors participants believed contributed to offending. It then analyzes the program and participants’ experiences, focusing on exercises about the mind (fantasy), Internet usage (disclosure and relationships), needs met by offending (Good Lives and true needs), and planning for the future (relapse prevention). Critical is that participants are encouraged to reengage offline lives and enact discipline on and to the online world. Thus, the article ends with an anthropologically-minded discussion about digital norms, online morality, and implications for Internet offender psychoeducational practice.